Determination of Lipophilic Marine Biotoxins in Mussels Harvested from the Adriatic Sea by LC-MS/MS - Schirone, Maria; Berti, Miriam; Visciano, Pierina; Chiumiento, Francesco; Migliorati, Giacomo; Tofalo, Rosanna; Suzzi, Giovanna; Di Giacinto, Federica; Ferri, Nicola (Frontiers in Microbiology, 2018)
Lipophilic marine biotoxins include okadaic acid, pectenotoxin, yessotoxin and azaspiracid groups. The consumption of contaminated molluscs can lead to acute food poisoning syndromes depending on the exposure level. Regulatory limits have been set by Regulation (EC) No 853/2004 and LC-MS/MS is used as the official analytical method according to Regulation (EU) No 15/2011. In this study specimens of mussels (Mytilus galloprovincialis) were collected along the coasts of the central Adriatic Sea during the years 2015-2017 and analyzed by the European harmonized Standard Operating Procedure. The method was validated for linearity, specificity, repeatability and reproducibility and it revealed able to be used for the detection of the lipophilic marine biotoxins. Levels of okadaic acid, pectenotoxin, yessotoxin and its analogues were detected at different concentrations in 148 (37%) out of a total of 400 samples, always below the maximum limits, except for 11 (4.3%) of them that were non-compliant because they exceeded the regulatory limit. Moreover, some samples were exposed to a multi-toxin mixture with regards to okadaic acid, yessotoxin and 1-Homo yessotoxin. Following these results, the aquaculture farms from which the non-compliant samples derived were closed until the analytical data of two consecutive samplings returned favorable. Besides the potential risk of consumption of mussels contaminated by lipophilic marine biotoxins, these marine organisms can be considered as bio-indicators of the contamination status of the marine ecosystem.